THE IMPACT OF ENVIRONMENTAL POLLUTION IN THE THOUSAND ISLANDS - Kerlima Hutagaol; Anugrah Ramadha Pratama; Fazry Alwy Sirodz; Purnama Ramdan; Angga Febriadi; Tiodorus Situmorang (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
The Thousand Islands, a key marine tourism destination in Indonesia, faces serious threats from environmental pollution. Plastic waste, oil spills, and unsustainable tourism activities damage the marine ecosystem, human health, and the socio-economic well-being of the local community. This study aims to examine the sources of pollution, its impacts, and mitigation efforts implemented in the Thousand Islands. The research method utilized a literature 1the primary pollution comes from microplastics, oil spills, and illegal tourism and fishing activities. This environmental damage reduces marine productivity, poses health risks, and fuels social inequality. Mitigation efforts need to be strengthened through plastic reduction policies, conservation education, and integrated waste management.